ISOLASI DAN IDENTIFIKASI SENYAWA METABOLIT SEKUNDER DARI FRAKSI ETIL ASETAT PADA DAUN BERWARNA MERAH PUCUK MERAH (Syzygium myrtifolium walp.). - Mila Wati; Erwin Erwin; Daniel Tarigan (JURNAL KIMIA MULAWARMAN, 2017)
The study aims to find secondary metabolites isolated from leave of pucuk merah (Syzygium Myrtifilium Walp). The method used is maceration, fractionation, column chromatography, thin layer chromatography and identified using Fourier Transform-Infra Red (FT-IR) and Gass Cromatography-Mass Spectroscopy (GC-MS). Phytochemical preliminary test of ethyl acetate fraction contained alkaloids, flavonoids, phenolic and triterpenoids, while the results of phytochemical test against stains 2 ethyl acetate fraction showed a positive test result contains the alkaloid compounds and compounds phenolic. The results of the analysis using cluster bonding FT-IR emergence OH (Hydroksi), C-H (Aromatic), CH3 (Aliphatic), and CO Ether, whereas the MS chromatograms obtained peak (peak) which have a similarity value above 90% according to willey09th.L database. estimates of the results of the analysis can be concluded that the stain 2 ethyl acetate fraction is estimated compound 2,4-di-tersier-butyl-fenol.